A 1904 episode in self-regulation: Arthur Lowes Dickinson and the development of the income statement. Issue 2 (November 2015) - Sasmaz, Mary B.
Abstract: This paper explores the impact that Sir Arthur Lowes Dickinson, inducted into the Accounting Hall of Fame in 1951, had on accounting thought in the United States. Throughout his career, Dickinson focused on improving the accounting profession, both internally and externally, through speeches, writing, and example. This paper takes particular focus on Dickinson's 1904 "The Profits of a Corporation" paper, his influence on governing bodies such as the Federal Reserve, and the long-term impact of his contribution to the current accounting profession and practice.